When Routines are Not Enough: Journalists' crisis management during the 22/7 domestic terror attack in Norway. (2nd April 2016) - Konow Lund, Maria; Olsson, Eva-Karin
Abstract : Interest in crisis management among journalism scholars grew in the wake of the terror attacks of September 11, 2001. Yet, few studies explore journalists and their organizations from a newsroom and organizational crisis management perspective. In this study, we study journalists' ability to conduct news work when faced with a frame-breaking news event—in this case, the July 22, 2011 attacks in Norway. Dividing the journalistic response to these events into three stages, each with its own particular challenges, we have been able to unpack how these Norwegian journalists were capable of reporting on the events despite the chaos and uncertainty that followed in their wake, including the fact that the newsroom itself suffered severe damage from the bomb blast. This study shows that coping mechanisms in times of organizational stress will range from the expected (routine, habit) to the unexpected (improvisation, bricolage). The individual must pick up where the organization leaves off, relying upon experience and professionalism as well as face-to-face interaction and the assistance of whatever technology survives.